Climate Change and Urban Water Utilities : Challenges and Opportunities - Danilenko, Alexander; Dickson, Eric; Jacobsen, Michael (World Bank, Washington, DC, 2012)
The impact of climate change is increasingly important for the design, construction, and maintenance of water sector infrastructure. Average global temperatures are on the rise, causing cycles of extreme weather: droughts and flooding are becoming common; seawater levels are rising; and many locations are considerably drier, impacting water sources such as lakes and rivers. Groundwater supplies are under stress due to decreasing precipitation rates and increasing extraction rates. Urban water systems must meet the demands of expanding industry needs and rapid population growth. Pollution adds to the growing threats to water resources, increasing treatment requirements for providing safe water to city residents. With two-thirds of the world's megacities located in regions that are vulnerable to the impacts of climate change, urban water utilities are facing an increasing need to improve the management of water resources and associated infrastructure. Diversifying sources of water supply will become increasingly important whether through the construction of new storage facilities, the appropriate and sustainable extraction of groundwater, water trading or conservation, or the use of recycled or desalinated water. This water note, based on the input of 20 large utilities around the world presents the perceptions, experiences, and approaches to addressing climate related challenges of urban areas in developing, middle income, and developed countries.